Uwarunkowania rywalizacji politycznej Platformy Obywatelskiej RP i Prawa i Sprawiedliwości - Maj, Przemysław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
The author presented the determinants of rivalry between PO and PiS. The analysis covered the genesis of both parties, existing and new socio-political divisions created by the parties; party memberships; differences in strategy and paradigms, and the differences of party programmes.
DETERMINANTS OF THE RIVALRY BETWEEN CIVIC PLATFORM AND LAW AND JUSTICE
Keywords: Civic Platform; Law and Justice; political competition; Polish political parties